The Development оf Human and Nature Relations in Philosophy - Mackevičiūtė, Jūratė (Problemos, 2000)
The article analyses an ecological problem from the philosophical standpoint. I discuss the way which led human reason has covered from the cosmological ideas to the concrete scientific investigations of the present ecological situation. Formerly the principle of naturalism only passively stated human identity with nature. Now it has turned into the ecological imperative. This principle is obligatory for all spheres of contemporary culture.
Keywords: naturalism; anthropocentrism; holism; ecological ethics